“It’s Feasible to Write a Song”: A Feasibility Study Examining Group Therapeutic Songwriting for People Living With Dementia and Their Family Caregivers - Clark, Imogen N.; Stretton-Smith, Phoebe A.; Baker, Felicity A.; Lee, Young-Eun C.; Tamplin, Jeanette (Frontiers in Psychology, 2020)
Background: Psychosocial interventions for people with dementia and their family caregivers together may sustain relationship quality and social connection. No previous music therapy research has examined the effects of group therapeutic songwriting (TSW) attended by people with dementia/family caregiver dyads. Method: This pre-post feasibility study aimed to examine the acceptability of a group TSW intervention for people with dementia/family caregiver dyads and test the sensitivity of the following outcomes: Quality of Caregiver Patient Relationship (QCPR, primary); Cornell Scale for Depression in Dementia (CSDD) and Quality of Life–Alzheimer’s Dementia for people with dementia; Patient Health Questionnaire-9, Assessment of Quality of Life-8 Dimensions (AQoL-8D), and Zarit Burden Scale for family caregivers. Six-weekly one-hour sessions guided participants to identify preferred music, brainstorm ideas, create lyrics, and record songs. Qualitative interviews were conducted with dyads who completed the intervention. Results: Fourteen dyads were recruited and completed baseline assessments. Participants with dementia were aged 62-92 years (M=77, SD=11). Caregiver participants (11 spouses, 2 daughters, 1 son) were aged 54-92 years (M=67, SD=10.1). Four dyads withdrew owing to declining health or inconvenience before the program commenced (n=2) and after attending 1-2 sessions (n=2). Ten dyads formed four homogeneous TSW groups (71% completion). No statistically significant changes were detected for any measures. High QCPR ratings at baseline (M=57.1) and follow-up (M=57.4) demonstrated sustained relationship quality. For participants with dementia, large effect sizes for the CSDD suggested trends towards decreased depression (d=-0.83) and improved mood (d=-0.88). For family caregivers, a large effect size suggested a trend towards improvement for the AQoL-8D sub-domain examining independent living (d=-0.93). Qualitative data indicated that session design and delivery were acceptable, and TSW was a positive shared experience with personal benefits, which supported rather than changed relationship quality. Conclusions: High retention and qualitative data indicate that TSW was well received by participants. Effect sizes suggest that group TSW for dyads may have beneficial impacts on depression for people with dementia and quality of life for family caregivers. Future research with a fully powered sample is recommended to further examine the psychosocial impacts of group TSW for people living with dementia/family caregiver dyads.